Impact of a Standardized Penicillin Allergy Assessment Program to Optimize Penicillin Allergy Documentation and Β-lactam Antibiotic Use at an Academic Medical Center. (4th October 2017) - Hanna, Sandra; Anderson, Deverick; Lugar, Patricia; Kleris, Renee; Moehring, Rebekah W; Wrenn, Rebekah; Sarubbi, Christina
Abstract: Background: The 2016 IDSA Guidelines for Implementing an Antibiotic Stewardship Program recommend that Antibiotic Stewardship Programs (ASPs) implement allergy assessments for patients with a documented penicillin allergy. The impact of completing these allergy assessments on allergy documentation and antibiotic prescribing is not well characterized. Methods: We performed a retrospective quasi-experimental study to evaluate the impact of the implementation of a standardized penicillin allergy assessment program by the Duke Antimicrobial Stewardship and Evaluation Team (ASET). Starting in May 2015, pharmacy technicians performed detailed assessments of admitted patients with a documented penicillin allergy; assessments were reviewed by clinical pharmacists. The pre-intervention period included randomly-selected adult patients with a reported penicillin allergy admitted from May 2014 to April 2015. The primary study outcome was accurate characterization of penicillin allergy within the electronic health record (EHR), including clarification of allergic reaction and removal of allergy. Secondary outcomes included B-lactam use within 90 days of hospitalization, time to complete the assessments, and hospital-wide aztreonam use, measured as days of therapy (DOT) per 1000 days present. Results: A total of 200 patients were included; 100 patients during the intervention period, and 100 during the pre-intervention period. The proportion of patients who had their allergy information updated increased from 31% to 62% following implementation of the program ( P < 0.0001); inappropriate allergy documentation was removed in 7 (7%) patients. The program did not change the percentage of study patients who received a B-lactam (24% vs. 26%; P = 0.74). Hospital-wide aztreonam use was lower in the intervention group (10.8 vs. 7.0 DOT/1, 000 days present; P < 0.0001). The average time to perform each assessment was 15 minutes. Conclusion: Implementation of a standardized penicillin allergy assessment program led to a significant impact on allergy documentation within the EHR without burdening pharmacy staff. While the rate of B-lactam therapy was unchanged, we observed a significant decrease in aztreonam utilization after program implementation. Disclosures: All authors: No reported disclosures.